Surgical Approach to a Large Left Adrenocortical Mass with Associated Tumour Thrombosis of the Left Renal Vein: Preservation of the Ipsilateral Kidney - Manuel Pérez Utrilla; Carlos Nuñez Mora; Alejandro Rojo Sebastián; Pedro M. Cabrera Castillo; José M. García Mediero (Advances in Urology)
A sixty-years-old male with diagnosis of a left adrenal mass (146×99×126 mm) with associated tumour thrombosis of the left renal vein with no clear signs of thrombosis of the inferior vena cava was admitted for elective surgery Finally an adrenalectomy and excision of tumour thrombus preserving the ipsilateral kidney was made. Despite of the complex vascular management, this kind of approaches allow to preserve normal renal function in patients with future nephrotoxic treatment like cisplatin.